2016
DOI: 10.1007/s12033-016-9950-1
|View full text |Cite
|
Sign up to set email alerts
|

The Modified Heparin-Binding l-Asparaginase of Wolinella succinogenes

Abstract: The modified asparaginase Was79 was derived from the recombinant wild-type L-asparaginase of Wolinella succinogenes. The Was79 contains the amino acid substitutions V23Q and K24T responsible for the resistance to trypsinolysis and the N-terminal heparin-binding peptide KRKKKGKGLGKKR responsible for the binding to heparin and tumor K562 cells in vitro. When tested on a mouse model of Fischer lymphadenosis L5178Y, therapeutic efficacy of Was79 was significantly higher than that of reference enzymes at all single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…L-ASNases from Rhodospirillum rubrum (RrA), Erwinia carotovora (ErA), Escherichia coli (EcA), and Wolinella succinogenes (WsA) were used. The upstream, downstream, and enzymatic properties of the studied enzymes were described previously [ 24 , 25 , 26 , 27 , 28 , 29 ]. Conjugation of L-ASNases with FITC was carried out according to a described protocol [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…L-ASNases from Rhodospirillum rubrum (RrA), Erwinia carotovora (ErA), Escherichia coli (EcA), and Wolinella succinogenes (WsA) were used. The upstream, downstream, and enzymatic properties of the studied enzymes were described previously [ 24 , 25 , 26 , 27 , 28 , 29 ]. Conjugation of L-ASNases with FITC was carried out according to a described protocol [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…Erwinia carotovora (Pectobacterium carotovorum) G281S Increased half-inactivation temperature; decreased catalytic activity for L-asparagine [76] Dickeya dadantii (Erwinia chrysanthemi) E63Q Decreased L-glutaminase activity [177] Dickeya dadantii (Erwinia chrysanthemi) D133V, D133L Higher thermal stability [73] Dickeya dadantii (Erwinia chrysanthemi) P285T Eight-fold reduced immunogenicity [99] Dickeya dadantii (Erwinia chrysanthemi) N41D, N281D Increased asparaginase activity and decreased L-glutaminase activity [81] Helicobacter pylori T16D Reduction of L-asparaginase and L-glutaminase activities [74] Helicobacter pylori Q63E Decreased glutaminase activity [74] Helicobacter pylori T95E Reduction of L-asparaginase and L-glutaminase activities [74] Helicobacter pylori M121C/T169M Undetectable L-glutaminase activity [133] Pyrococcus furiosus K274E Increased L-asparaginase activity, resistance to proteolytic digestion and no displayed glutaminase activity [80] Rhodospirillum rubrum D60K, F61L Improvement of kinetic parameters and enzyme stabilization [178] Rhodospirillum rubrum E149R, V150P, F151T Able to reduce the expression hTERT subunit of telomerase and suppress telomerase activity [24,25,163] Saccharomyces cerevisiae T64A, Y78A, T141A, K215A 99.9% loss of activity [179] Wolinella succinogenes V23Q, K24T Resistance to trypsin degradation, decreased glutaminase activity and reduced immunogenicity [170]…”
Section: Source Mutations Results Achievedmentioning
confidence: 99%
“…Modified heparin-binding L-ASNase from Wolinella succinogenes (Was79) contains amino acid substitutions V23Q and K24T, which resist trypsin, and the N-terminal heparin-binding peptide KRKKKGKGLGKKR, which is responsible for binding to heparin and to tumor cells in vitro [ 129 , 170 ]. When tested on a mouse model of Fischer’s lymphadenosis L5178Y, the therapeutic efficacy of Was79 was significantly higher than that of the reference enzymes.…”
Section: Alternative Approaches To the Development Of Antitumor L-asn...mentioning
confidence: 99%
“…One of the most used promoters is T7 (from bacteriophage T7) due to the extensive use of the pET expression system. Most studies reported on L-ASNase production are based on the use of pET systems (Aghaeepoor et al, 2011;Cappelletti et al, 2008;Chohan & Rashid, 2013;Costa et al, 2016;Ghoshoon et al, 2015;Goswami et al, 2019;Hong et al, 2014;Huang et al, 2014;Jiao et al, 2020;Khushoo et al, 2005;Kotzia & Labrou, 2007;Maqsood et al, 2020;Radha et al, 2018;Roth et al, 2013;Saeed et al, 2018;Sannikova et al, 2016;Shakambari et al, 2018;Upadhyay et al, 2014;Vidya & Pandey, 2012;Zuo et al, 2014). This is mainly due to the power of this promoter, significantly increasing transcription levels.…”
Section: Engineering Of Promoters To Improve the Transcription Of Asn...mentioning
confidence: 99%
“…These tags are summarized in Table 2. Sannikova et al (2016) produced in E. coli BL21(DE3) a modified form of wild L-ASNase derived from Wolinella succinogenes . Was79 L-ASNase had two substitutions of different amino acids: first, V23Q and K24, which was resistant to trypsin lysis.…”
Section: Use Of Fusion Tagsmentioning
confidence: 99%